New Possibilities on the Horizon: Genome Editing Makes the Whole Genome Accessible for Changes - Kawall, Katharina (Frontiers in Plant Science, 2019)
The emergence of new genome editing techniques, such as the site-directed nucleases, clustered regulatory interspaced short palindromic repeats (CRISPRs)/Cas9, transcription activator-like effector nucleases (TALENs), or zinc finger nucleases (ZFNs), has greatly increased the feasibility of introducing any desired changes into the genome of a target organism. The ability to target a Cas nuclease to DNA sequences with a single-guide RNA (sgRNA) has provided a dynamic tool for genome editing and is naturally derived from an adaptive immune system in bacteria and archaea. CRISPR/Cas systems are being rapidly improved and refined, thereby opening up even more possibilities. Classical plant breeding is based on genetic variations that occur naturally and is used to select plants with improved traits. Induced mutagenesis is used to enhance mutational frequency and accelerate this process. Plants have evolved cellular processes, including certain repair mechanisms that ensure DNA integrity and the maintenance of distinct DNA loci. The focus of this review is on the characterization of new potentials in plant breeding through the use of CRISPR/Cas systems that eliminate natural limitations in order to induce thus far unachievable genomic changes.